(untitled) (Development Service Industry Management, 2025)
In the context of the new economic reality, personnel management acquires special importance, since it is the quality of human resources, its motivational component, the level of professional training, and the ability to adapt that determine the competitiveness and long-term viability of an enterprise. Survival and successful development of hotel and restaurant entities in conditions of constant market turbulence are possible only if effective, scientifically based methods of personnel management are implemented, focused on the development of innovative competencies, the formation of corporate culture, and maintaining a high level of organizational flexibility. Therefore, modern business realities highlight the need for a creative, systematic, and analytical approach to the formation of personnel policy. Scientific support for personnel management processes is an important tool for increasing the efficiency of the functioning of enterprises in the hotel and restaurant sectors, which allows not only to adapt to changing environmental conditions, but also to form a sustainable competitive advantage in the services market. That is why the purpose of the study is to identify modern approaches to personnel management in the hotel and restaurant business. To achieve the set goal, a competency model for a manager of hotel and restaurant enterprises was outlined, factors that influence the effectiveness of a manager’s professional growth and measures for the practical use of leadership in the hotel and restaurant business were identified.